Effect of Ca2+ signaling pathway on leaf position-associated resistance to Sclerotinia sclerotiorum in Nicotiana benthamiana - Lü Linhui; Xu Youping; Ren Zhixuan; Kang Dong; Wang Jipeng; Cai Xinzhong (浙江大学学报. 农业与生命科学版)
Leaf position significantly affects plant disease resistance. The majority of known examples demonstrate that plants are generally more susceptible to disease in lower leaves than upper leaves. Among them there are the resistances of cabbage to Hyaloperonospora parasitica, tomato to Phytophthora infestans and adlay to Bipolaris coicis. The exception is grapevine-Uncinula necator pathosystem where the lower leaves show a higher resistance to powdery mildew pathogen U. necator than the upper leaves. To date, the molecular mechanisms controlling leaf position-associated resistance remain unclear. Sclerotinia sclerotiorum (Lib.) de Bary is one of the most destructive plant pathogenic fungi in the world. The white mould/stem rot disease caused by S. sclerotiorum is a serious world-wide problem, resulting in a huge yield loss every year. On the other hand, the role of Ca2+ signaling pathway in plant disease resistance has been revealed. Nevertheless, whether it affects the leaf position-associated resistance is still unclear.The aim of this study was to investigate the effect of leaf position on resistance of Nicotiana benthamiana to S. sclerotiorum and to further reveal the role of Ca2+ signaling pathway in this leaf position-associated resistance and thus to improve the understanding of the molecular mechanisms underlying this resistance.The effect of leaf position on the resistance of N. benthamiana to S. sclerotiorum was analyzed by comparison among the resistance of leaves at various positions in the same plants, which was evaluated through inoculation experiments. Contribution of Ca2+ signaling pathway to this leaf position-associated resistance was demonstrated through three layers of assays, pharmacological assay to make clear effect of Ca2+ channel inhibitors LaCl3 and NaVO3 on leaf position-associated resistance, quantitative reverse transcriptase-polymerase chain reaction (qRTPCR) assay to probe the expression of three Ca2+ signaling-related genes NbCNGC20, NbCAMTA3 and NbCML1 in leaves at different positions and virus-induced gene silencing (VIGS) assay to explore the effect of the Ca2+ signaling-related gene NbCML1 on leaf position-associated resistance to S. sclerotiorum in N. benthamiana.The results of inoculation experiments showed that the leaf position significantly influenced the resistance of N. benthamiana to S. sclerotiorum. The upper, middle and lower leaves of 12-leaf-stage plants formed lesions of 18.0 mm, 13.7 mm and 11.9 mm at diameter, respectively. This demonstrates that the resistance increases in leaves of positions from upper to lower, which is in contrast to most of the reported pathosystems. When pre-infiltrated with 1 mmol/L LaCl3 and 50 μmol/L NaVO3, leaves at different positions exhibited lesions of larger size in comparison with those of the untreated control plants, indicating that the two inhibitors of Ca2+ signaling eliminate the leaf position-associated resistance to S. sclerotiorum in N. benthamiana. Additionally, the expression of genes NbCNGC20, NbCAMTA3 and NbCML1 varied obviously in leaves at different positions, and all of them were increased from upper to lower leaves. Moreover, in NbCML1-silenced plants, all leaves of different positions displayed lesions of larger size, when compared with those of the non-silenced control plants, revealing that the silencing of NbCML1 in N. benthamiana erases the leaf position-associated resistance to S. sclerotiorum.In summary, the data of this study reveal that leaf position significantly affects the resistance of N. benthamiana to S. sclerotiorum. In contrast to most of the reported pathosystems, this resistance is much stronger in lower leaves than in upper ones. Our finding demonstrates that the magnitude trend of leaf position-associated resistance in leaves of various positions is pathosystem-dependent. Furthermore, this study unveils that Ca2+ signaling pathway, including NbCML1, makes great contribution to the leaf position-associated resistance to S. sclerotiorum in N. benthamiana. This finding provides new insights into molecular mechanisms underlying the leaf position-associated resistance.